2012
DOI: 10.1111/j.1553-2712.2012.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

When an Event Sparks Behavior Change: An Introduction to the Sentinel Event Method of Dynamic Model Building and Its Application to Emergency Medicine

Abstract: Experiencing a negative consequence related to one’s health behavior, like a medical problem leading to an emergency department visit, can promote behavior change, giving rise to the popular concept of the “teachable moment.” However, the mechanisms of action underlying this process of change have received scant attention. In particular, most existing health behavior theories are limited in explaining why such events can inspire short-term change in some, and long-term change in others. Expanding on recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 22 publications
5
77
0
Order By: Relevance
“…Furthermore, due to ethical considerations control group participants received some kind of an active intervention in all studies included in this review, potentially contributing to a systematic underestimation of effects under real-world conditions. On the other hand, it is also possible that the ED visit itself represents an event that triggers behaviour change [65] in a way that BIs do not add a significant additional effect, potentially even more so for young individuals treated following an alcohol-related event. Segatto et al [46] reported the only RCT that did not find positive effects of the BI on any outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to ethical considerations control group participants received some kind of an active intervention in all studies included in this review, potentially contributing to a systematic underestimation of effects under real-world conditions. On the other hand, it is also possible that the ED visit itself represents an event that triggers behaviour change [65] in a way that BIs do not add a significant additional effect, potentially even more so for young individuals treated following an alcohol-related event. Segatto et al [46] reported the only RCT that did not find positive effects of the BI on any outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Across many medical settings, it is quite common to observe sudden, unplanned behavior change after an acute illness or diagnosis (Boudreaux, Bock, & OHea, 2012). In a compelling exposition of the relation between medical events and smoking cessation, McBride and colleagues (2003) point out that several indirect lines of evidence converge to support the premise that sentinel health events can trigger behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…Using smoking as an illustrative example, they noted that patients who experience an important health event, such as pregnancy, hospitalization, or a serious disease diagnosis, have significantly higher rates of cessation than the general population, or patients simply attending an outpatient clinic appointment or well visit. Boudreaux and colleagues (2012) have also demonstrated that patients experiencing medical emergencies, like myocardial infarctions, who are assigned to control conditions in clinical trials can still exhibit long-term cessation rates. The Sentinel Event Model (SEM; Boudreaux et al, 2012) theorizes that cognitive and emotional factors interact, and change over time, after a health event and thus result in health behavior change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond simply acting as an entry point to primary care, emergency physicians can provide the first crucial steps in managing these conditions, and coordinate follow-up care with outpatient clinics. An ED visit may act as a "sentinel event" and has the potential to effect long-term changes in patient behaviour (20).…”
Section: Future Directionsmentioning
confidence: 99%